Microplastic ingestion cause intestinal lesions in the intertidal fish Girella laevifrons. (February 2020) - Ahrendt, C.; Perez-Venegas, D.J.; Urbina, M.; Gonzalez, C.; Echeveste, P.; Aldana, M.; Pulgar, J.; Galbán-Malagón, C.
Abstract: We exposed juvenile intertidal fish to different amounts of Poly(styrene- co -divinylbenzene) microplastics in their diet. We fed ten individuals with pellets containing 0.01 g, another ten fish with pellets containing 0.1 g of PS, and ten fish without plastic as control. After 45 days of treatment, the whole intestine was removed, and the histological evaluation started immediately. We evaluated inflammation due to leukocyte infiltration (Lk), circulatory disorders like Hypermeia (Hyp), and regressive changes in the intestinal tissue, assessing Crypt cell loss (Ccl) and Villi cell loss (Vcl). The severity of the lesions increased according to the microplastic concentration. In the fish group feeding on microplastics, we found that leukocyte infiltration and hyperemia were more severe in the higher exposure group compared to the lower exposure; and crypt cell loss and villi cell loss increased significantly due to Poly(styrene- co -divinylbenzene) microplastic physical abrasion. Graphical abstract: Unlabelled Image Highlights: Individuals of Girella laevifrons were exposed to increasing amounts of polyestyrene nano particles. No nano particles of PS were found in the control, but occurrence increased in exposed animals. The severity of hyperemia, leukocyte infiltration, and villi and crypt cell loss increased with exposure.